The Influence of The Subdistrict Head’s Servant Leadership on Employees’ Work Initiative and Service Orientation at the Eromoko Subdistrict Office, Wonogiri Regency - Ernawati; Zandra Dwanita Widodo; Atik Lusia (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This study aims to analyze the influence of the subdistrict head’s Servant Leadership style on employee work behavior, particularly in terms of work initiative and service orientation. The background of this research arises from the need for local bureaucracy at the subdistrict level to provide public services that are responsive, friendly, and oriented toward citizen satisfaction, while simultaneously encouraging employees to be more proactive and innovative in carrying out their duties. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews with five key informants, participatory observation of service activities, and documentation of organizational archives and internal reports. Thematic analysis was conducted through stages of open coding, axial coding, and selective coding, which were then visualized in conceptual diagrams to illustrate the relationship between leadership, employee initiative, and service orientation. The findings reveal that the subdistrict head’s leadership behavior, emphasizing empathy, role modeling, and empowerment, contributes to the development of a humanistic, proactive, and service-oriented work culture. Employees who feel involved and supported tend to demonstrate high initiative, such as working without waiting for instructions, innovating, and enhancing competencies. Conversely, employees who perceive leadership as more administrative tend to exhibit passive work behavior limited to routine tasks. This study concludes that Servant Leadership has a multidimensional impact on employees, both in shaping service orientation that is friendly and responsible, and in fostering work initiative that is professional and effective. These findings provide theoretical contributions to the development of Servant Leadership concepts in local bureaucracy, as well as practical implications for improving the quality of public services at the subdistrict level.